Two-round Fill-up Method for Feature Extraction in Complex Watersheds and Its Application to the Pearl River Basin - WANG Jiahu; PU Wenjie; DU Jiayang; ZHANG Wenming; LI Li (Renmin Zhujiang)
Digital watershed feature extraction is an essential foundation for distributed hydrological process simulation and also a basis for constructing a "digital twin" water conservancy project. To minimize the disturbance of river data to the original digital elevation model (DEM) and improve the calculation speed, this paper adopts the two-round fill-up method for the Pearl River Basin. The river rasters and the whole-basin rasters are filled separately. The flow direction of the main river network is determined first, and then the rasters of the main river network and the regional boundaries are used as the exits for the fill-up of the whole basin to get the flow directions of all the rasters and determine the digital watersheds. Compared with the manually digitized watersheds, the results of this paper show the total area error of -11.0%, of which the area error of the Dongjiang River is -3.6%, and that of the Xijiang River is -2.5%, having an obvious advantage, compared with similar products (HydroSHEDS and Zhonghong System backstage data). The method of this paper can improve the precision and accuracy of watershed feature extraction to a certain extent and has significant application value.